2011
DOI: 10.1002/ejic.201001225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cp*2Ti(OTf) and Its Reaction with Water

Abstract: Cp*2Ti(OTf) (2) was prepared by oxidation of the known(alkyne)titanocene complex Cp*2Ti(η2‐Me3SiC2SiMe3) with Fe(OTf)3. This reaction is highly selective; formation of Cp*2Ti(OTf)2 by using an excess of the oxidizing agent was not observed. Complex 2 was treated with water to give Cp*2Ti(OH)(OTf) (5) and hydrogen gas. This reaction was monitored by GC and volumetric analysis. Complexes 2 and 5 were characterized by X‐ray crystallography and investigated by DFT analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 30 publications
4
50
1
3
Order By: Relevance
“…This corresponds to the conditions applied previously. [5] Without added water, the spectrum of 1 in THF shows characteristic bands at 1339, 1234, 1201, and 1177 cm À1 resulting from the OTf ligand ( Figure 1). [12,13] From FTIR spectroscopic investigations of ionic and coordinated OTf it is known that the nA C H T U N G T R E N N U N G (SO 3 ) band of free ionic OTf À appears at about 1270 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to the conditions applied previously. [5] Without added water, the spectrum of 1 in THF shows characteristic bands at 1339, 1234, 1201, and 1177 cm À1 resulting from the OTf ligand ( Figure 1). [12,13] From FTIR spectroscopic investigations of ionic and coordinated OTf it is known that the nA C H T U N G T R E N N U N G (SO 3 ) band of free ionic OTf À appears at about 1270 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…This proposed mechanism was corroborated by the existence of similar water-ligated titanocene cations, which have Abstract: A detailed mechanism of hydrogen production by reduction of water with decamethyltitanocene trif-A C H T U N G T R E N N U N G late [Cp* 2 Ti III A C H T U N G T R E N N U N G (OTf)] has been derived for the first time, based on a comprehensive in situ spectroscopic study including EPR and ATR-FTIR spectroscopy supported by DFT calculations. It is demonstrated that two H 2 Keywords: density functional calculations · EPR spectroscopy · hydrogen production · IR spectroscopy · titanium · water activation [ [5] and oxidation (L = H) [6] with titanium complexes.…”
Section: ]A C H T U N G T R E N N U N G [Otf] (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of the ansa-titanocene dichloride [12] 2-Cl 2 proceeds through a transmetallating salt metathesis from complex 1 and [ 3 ] as demonstrated before by Tacke and co-workers, [16] followed by subsequent oxidation with PbCl 2 (Scheme 2). The product complex 2-Cl 2 can be obtained as dark red, air-stable crystals in high yields.…”
Section: Resultsmentioning
confidence: 99%
“…[2] The latter inspired us to investigate the reactivity of titanocene compounds towards water regarding the elemental steps of water splitting and hydrogen evolution. [3] More recently, we addressed the second, probably more challenging part of overall water splitting, that is, water oxidation, by using the hydroxyl-bearing titanocene [Cp* 2 Ti(OH) 2 ]. [3] More recently, we addressed the second, probably more challenging part of overall water splitting, that is, water oxidation, by using the hydroxyl-bearing titanocene [Cp* 2 Ti(OH) 2 ].…”
Section: Introductionmentioning
confidence: 99%